Intermetallic thickness and physical studies of Sn-3.5Ag-1.0Cu lead free solder with ni addition / Noor Asikin Ab Ghani - Ab Ghani, Noor Asikin (2016)
Due to the environmental and health concern, the use o f lead free solder has been introduced in 2000 by National Electronics Manufacturing Initiative (NEMI) to replace the tin-lead (Sn-Pb) solder. Among many lead free solders, the tin-silvercopper (Sn-3.5Ag-l.0Cu) is a potential replacement for Sn-Pb because it has a good compatibility with common commercial components and low melting point compared with other lead free solders. This research was carried out to study the properties of Sn-3.5Ag-l.0Cu solder by adding three different amount o f Ni into the solder which was characterized for its melting temperature, density and hardness test. The melted solder was aged in an oven until 1000 h for intermetallic and joint strength study. Intermetallic formation was analyzed under the Scanning Electron Microscope (SEM) and Energy Dispersive X-ray (EDX). Shear joint sample was tested using an instron machine. The onset temperature slightly increases to 220.3°C and liquidus temperature and pasty range decrease to 233.6°C and 13.3°C. 2 h mixing time and 14 MPa pressure are an optimum condition for sample preparation. The addition o f Ni retards the growth o f intermetallic with 0.05 wt.% Ni the most significant value compared to 0.2 and 0.5 wt.% Ni. 0.05 and 0.2 wt.% Ni give the smallest and similar total growth rate constant (A) which is 10.240x1 O'14 cm2/s. Smallest growth rate values indicate the smallest diffusion coefficient reaction between solder and substrate during aging process, retards the intermetallic thickness which influence solder joint strength. Stress and strain values increase with the decreasing o f intermetallic thickness. 0.05 wt.% Ni has the highest stress and strain values which are 21.52 MPa and 0.118.